THE ROLE OF SOCIAL MEDIA IN STRENGTHENING THE BOYCOTT MOVEMENT OF ISRAELI PRODUCTS DURING THE ISRAEL-PALESTINE WAR 2023-2024 - Nurfaedah, Nurfaedah; Mustikasari, Molly; Sehabudin, Dedeng (Komitmen: Jurnal Ilmiah Manajemen, 2025)
This research aims to find out the mechanism of social media in the boycott of Israeli and American products since Israel's brutal attack on Palestine in 2023, the attacks carried out by Israel against Palestine have claimed thousands of civilian victims. This issue concerns humanity, where the oppression of fellow human beings is a violation of human rights, even genocide. Research that uses a qualitative approach, library research. The result is one of social media, Instagram, has an important role in increasing boycotts by people around the world. It is able to reduce the value of shares and profits of well-known companies affiliated with Israel. It is caused by social media in the boycott is supported by live video shows, photos and narratives that describe all Israeli crimes against Palestine strengthened by the algorithm. The process of share, shape, boycott and algorithm become integrated, accelerate and the success stages.